OMPARAÇÃO ENTRE RESULTADOS COMPUTACIONAIS E EXPERIMENTAIS DO COMPORTAMENTO TÉRMICO DE UM AMBIENTE - de Oliveira Grings y Col., Edi Terezinha (2019)
This work presents a comparison between computational results, obtained through the use of the software EnergyPlus, and experimental results of the thermal behavior of an air-conditioned and non-air-conditioned environment. In order to do that, climatic data on radiation, wind speed and temperature were monitored in the period between the 11 and 20 of January 2002 and a climatic. Simultaneously, the temperatures of a test-room, situated on the 3rd floor of a building in the town of Porto Alegre, were collected. The suply and return temperatures of the air conditioners, situated in the testroom, were measured during the day, in 6 days of the monitoring period. The return air speed was measured and refrigeration sensitive capacity calculated. The results of the thermal load and the environmental temperature of the testroom obtained in the simulations were compared with the experimental data. There was a good agreement between thecomputational and experimental results.